Acceptability of Cookies with Substitution of Indian Mackerel Flour (Rastrelliger kanagurta) and Moringa Leaf FlourOrganoleptic Test Of Cookies with Subtitution Of Mackerel Flour (Rastrelliger sp.) And Moringa Leaf Flour - Ludji, Emmy Tertaliana; Jutomo, Lewi; Ndoen, Honey Ivon (Universitas Nusa Cendana, 2023)
Cookies are dry cakes with low water content, which are widely consumed among the public. The content in Indian mackerel and Moringa leaves is believed to increase the nutritional value of cookies so that they can be declared functional cookies with various benefits for the body. This study aimed to analyze the levels of water content and acceptability of cookies by adding Indian mackerel flour and Moringa leaf flour. This research is an experimental study with a simple Completely Randomized Design (CRD) with treatment levels of 0%, 15%, 30%, and 45%. The design of this study was made by making comparisons and adding Indian mackerel flour and moringa leaf flour with four treatments and three repetitions. Testing the water content using proximate analysis, while the organoleptic test was obtained from the panelist assessment results. The results showed that the substitution of Indian mackerel flour and moringa leaf flour had a significant effect on the water content and the acceptability of the texture and color of the cookies. Still, no effect was found on taste acceptability 0.843 (p>0.05), and cookie aroma 0.214 (p>0.05). This study concludes that cookies P2 (15%) are the recommended type of cookies because, in terms of taste and aroma, they get the highest preference rating by the panelists.